This river beneath the sky : a year on the Platte - Pfost, Doreen (University of Nebraska Press, 2016)
"Each spring, formations of sandhill cranes crisscross the skies along Nebraska's Platte River in one of the last great migratory spectacles on the North American continent. From across the globe, tens of thousands of visitors gather to witness a land transformed, 'wild with birds.' But the central Platte River system is witness to even more than this wondrous annual event. It is also an abiding source of natural, agricultural, and economic life in three states as an icon of western history and as a place of wonder. In This River Beneath the Sky, Doreen Pfost seamlessly blends memoir and nature writing, tracking the Platte River valley for one calendar year, ushering readers through its diverse and changing landscape and the plants, animals, and humans that call the ecosystem home. From serving as a tour guide for visitors who come to see the sandhill crane migration to monitoring the population count on a bluebird trail, from exploring the human settlements surrounding the Platte River to wading the river with biologists, Pfost immerses herself in the rhythm and life of the area. Along with Pfost's personal experiences of the river, she explores the river's history, the land- and water-use choices that were made decades ago and their repercussions that must now be mitigated if cranes--and other species--are to survive and flourish, and the legislative and scientific efforts to preserve the diverse species and their essential habitat"--